2006
DOI: 10.1051/kmae:2006015
|View full text |Cite
|
Sign up to set email alerts
|

Shelter Competition Between Two Invasive Crayfish Species: A Laboratory Study

Abstract: Alien crayfishes represent a common threat to aquatic ecosystems. Their spread in Europe is leading to more frequent contacts between different invasive species populations. Shelter can be an important factor in the resulting interactions. A laboratory experiment was designed to analyse the competition for shelter in similarly sized males of two species that show an invasive behaviour in Spain, Pacifastacus leniusculus and Procambarus clarkii.We carried out 24 heterospecific, six-hour trials, with 30 min behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In River Maçãs, the temperature tolerance limits of both species are never exceeded but minimum temperatures and possibly other environmental dimensions related to the upriver conditions affect P. clarkii more than P. leniusculus and seem the most probable cause for the observed differences of CPUE and species proportions. Laboratory studies showed P. clarkii wins agonistic interactions (Figler et al, 1995(Figler et al, , 1999Gherardi et al, 1999;Gherardi and Daniels, 2004;Alonso and Martínez, 2006) which strongly support the hypothesis that P. leniusculus dominance in most river sectors and the upper limit of P. clarkii distribution is mostly the result of environmental conditions. The persistence of the crayfish coexistence remains to be seen and as both species are generalists and potential invaders, coexistence is expected to persist where both species face some degree of environmental stress, i.e., no dominance and displacement will happen because neither of them lives under optimal conditions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In River Maçãs, the temperature tolerance limits of both species are never exceeded but minimum temperatures and possibly other environmental dimensions related to the upriver conditions affect P. clarkii more than P. leniusculus and seem the most probable cause for the observed differences of CPUE and species proportions. Laboratory studies showed P. clarkii wins agonistic interactions (Figler et al, 1995(Figler et al, , 1999Gherardi et al, 1999;Gherardi and Daniels, 2004;Alonso and Martínez, 2006) which strongly support the hypothesis that P. leniusculus dominance in most river sectors and the upper limit of P. clarkii distribution is mostly the result of environmental conditions. The persistence of the crayfish coexistence remains to be seen and as both species are generalists and potential invaders, coexistence is expected to persist where both species face some degree of environmental stress, i.e., no dominance and displacement will happen because neither of them lives under optimal conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Policar and Kozák, 2005;Gallagher et al, 2006), traps are still the most frequently employed method of capturing crayfish Momot and Gowing, 1972;Byrne et al, 1999;Demers and Reynolds, 2002;Flotemersch and Jackson, 2003;Lyons and Kelly-Quinn, 2003;Martínez et al, 2003;Yamamoto, 2010). Previous studies have shown variable levels of aggression among different crayfish species (Figler et al, 1995(Figler et al, , 1999Gherardi et al, 1999;Gherardi and Daniels, 2004;Tierney et al, 2000;Alonso and Martínez, 2006;Luan, 2009) and in situations of coexistence, traps may underestimate the abundance of the less aggressive species. Electrofishing is possibly a more effective technique to detect and sample crayfish (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Vorburger and Ribi 1999), to account for the effect of body size and mass pairs were matched so that differences between pair members did not exceed 10% for all three compared measurements (W, CL and RCL), as in other dyadic studies of crayfish interactions (e.g. Söderbäck 1991;Schroeder and Huber 2001;Alonso and Martinez 2006;Fero et al 2007 etc.). Before the start of each laboratory trial, crayfish were kept in total isolation for 24 h during which each individual was kept in separate plastic tank with aerated water.…”
Section: Pairwise Experiments-general Proceduresmentioning
confidence: 99%
“…Lodge et al ., ; Nyström, Brönmark & Granéli, ). Invasive species of crayfish regularly outcompete and replace native crayfish (Hill & Lodge, ; Alonso & Martínez, ; Dunn et al ., ; Haddaway et al ., ), but interactions among invasive crayfish are rarely examined despite the increasing likelihood of them occurring in sympatry. While competition has resulted in serial replacement of invasive crayfish in some instances (Hill & Lodge, ), coexisting populations are known (Nakata et al ., ; Bernardo et al ., ), but their combined interactive effect on the ecosystem is unknown.…”
Section: Introductionmentioning
confidence: 99%